2012
DOI: 10.1159/000338830
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and Substance Abuse Comorbidity: Nicotine Addiction and the Neonatal Quinpirole Model

Abstract: This review focuses on nicotine comorbidity in schizophrenia, and the insight into this problem provided by rodent models of schizophrenia. A particular focus is on age differences in the response to nicotine, and how this relates to the development of the disease and difficulties in treatment. Schizophrenia is a particularly difficult disease to model in rodents due to the fact that it has a plethora of symptoms ranging from paranoia and delusions of grandeur to anhedonia and negative affect. The basis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 189 publications
(109 reference statements)
2
19
0
Order By: Relevance
“…Given that schizophrenia spectrum disorders including schizotypy are frequently comorbid with anxiety and affective disorders [Anticevic et al, ; Buckley et al, ; Samsom and Wong, ; Zink, ] as well as substance abuse [Brown et al, ; Regier et al, ; Thoma and Daum, ], the specificity of the associations between connectivity and schizotypy observed here remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…Given that schizophrenia spectrum disorders including schizotypy are frequently comorbid with anxiety and affective disorders [Anticevic et al, ; Buckley et al, ; Samsom and Wong, ; Zink, ] as well as substance abuse [Brown et al, ; Regier et al, ; Thoma and Daum, ], the specificity of the associations between connectivity and schizotypy observed here remains to be clarified.…”
Section: Discussionmentioning
confidence: 97%
“…Environmental, social, and inflammatory challenges during sensitive periods of forebrain development also produce neuro(mal)adaptions in these regions and phenocopy some aspects of brain disorders (Di Forti et al, 2007; Kern et al, 2010; Han et al, 2012; Selemon and Friedman, 2013). For example, models of prenatal infection, stress, and exposure to drugs of abuse show long-lasting changes in DA receptor expression and function and have been associated with increased risk for psychiatric disorders (Alonso et al, 1994; Stanwood et al, 2001b; Berger et al, 2002; Zuckerman et al, 2003; Andersen and Teicher, 2009; Bhide, 2009; Brown et al, 2012). Taken together, these data have led our group and others to hypothesize that DAergic modulation of developmental processes produces long lasting alterations that contribute to cortical and striatal dysfunction in neuropsychiatric disorders.…”
Section: Developmental Effects Of Dopaminergic Modulationmentioning
confidence: 99%
“…We have shown that NQ treatment in rats leads to enhanced behavioral and dopaminergic response to nicotine [4] as well as to amphetamine [5,6]. We have also validated NQ treatment as a model of psychosis in several other behavioral and neurobiological domains [7], meeting all standards of model validity [8]. Important to the present study, individuals diagnosed with schizophrenia are 3-4 times more likely to smoke cigarettes compared to the normal population [9,10], but there is no delineated mechanism for this increase.…”
Section: Introductionmentioning
confidence: 94%